2005
DOI: 10.1002/app.22157
|View full text |Cite
|
Sign up to set email alerts
|

Reduced shrinkage polyester–montmorillonite nanocomposite

Abstract: A new approach is described for utilizing the swelling characteristics of montmorillonite (MMT) to compensate for polymerization-induced shrinkage in unsaturated polyester. The naturally sorbed sodium cation, at the lamellar interface of the mineral, was exchanged with the onium salt of 12-aminolauric acid to produce organophilic MMT, which was compatible with the host resin. The latter, boosted by a small amount of dimethylformamide, swelled into a polymerizing polyester resin, thus reducing polymerization sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Recently, special attention has been paid to the properties of nanocomposites. These properties include physical and mechanical properties [1, 2], thermal and electrical properties [3, 4], flame retardancy [5–7], gas barrier properties [8, 9], and shrinkage control behavior [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, special attention has been paid to the properties of nanocomposites. These properties include physical and mechanical properties [1, 2], thermal and electrical properties [3, 4], flame retardancy [5–7], gas barrier properties [8, 9], and shrinkage control behavior [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…12). At the same magnification, the fracture surface was not found to have any MMT domains, and the corresponding elemental mapping for silicon did not show any agglomeration, which suggested that the SVP(66THF)MMT agglomerates were dissociated to much smaller particles whose sizes were well below the SEM resolution 29. This conclusion was in accord with the XRD data that the highest MMT expansion occurred when the clay modification was done in the solvent mixture with 66% THF (Table II), which resulted in exfoliation with the nanoscale dispersion of clays.…”
Section: Resultsmentioning
confidence: 96%
“…Shrinkage control by application of nanoclays without any further addition of thermoplastic LPA to UPR was reported to also be possible; here, the "swelling clay" property of montmorillonite (MMT) has been exploited by adding 5% of 12-aminolauric acid MMT to an isophthalic UPR to reduce the volume contraction from 8.7% shrinkage of the neat resin to 2.6% shrinkage of the UPR nanocomposite [154]. In this case, curing was performed at 85°C.…”
Section: Upr Shrinkagementioning
confidence: 97%